2010
DOI: 10.1002/jat.1502
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of gentamicin‐induced nephrotoxicity: trimetazidine versus N‐acetyl cysteine

Abstract: Gentamicin (G) is a highly nephrotoxic aminoglucoside. It was used to experimentally induce nephrotoxicity in male Wistar rats. To find a drug capable of protecting the nephron we assayed a cardioprotector (trimetazidine, TMZ) and a hepatoprotector (N-acetyl cysteine, NAC). The rats were divided into six groups (n = 8): (A) control without drugs; (B) treated with 50 mg kg(-1) per day (i.p.) of G for 7 days; (C) diet supplemented with 20 mg kg(-1) per day of TMZ for 7 days; (D) treated with 10 mg kg(-1) per day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…These effects have been experimentally assessed in various models including cell cultures, isolated tissues, and different perfused organs. It was found to decrease IRI in an animal model of acute renal failure, 29,30 gentamicininduced nephrotoxicity, 31 and CIN in the studies included in this analysis. With regard to IRI, TMZ was shown to prevent the mitochondrial membrane dissipation, restore nicotinamide adenine dinucleotide phosphate levels, decrease Ca 2þ -induced mitochondrial swelling, restore glutathione peroxidase levels, 32 and enhance the expression of hypoxia-inducible factor 1a.…”
Section: Discussionmentioning
confidence: 87%
“…These effects have been experimentally assessed in various models including cell cultures, isolated tissues, and different perfused organs. It was found to decrease IRI in an animal model of acute renal failure, 29,30 gentamicininduced nephrotoxicity, 31 and CIN in the studies included in this analysis. With regard to IRI, TMZ was shown to prevent the mitochondrial membrane dissipation, restore nicotinamide adenine dinucleotide phosphate levels, decrease Ca 2þ -induced mitochondrial swelling, restore glutathione peroxidase levels, 32 and enhance the expression of hypoxia-inducible factor 1a.…”
Section: Discussionmentioning
confidence: 87%
“…Trimetazidine (TMZ), 1-2,3,4 tri-metoxibencil piperazine dihydrochloride, is a clinically available drug used for ischemic heart disease because it prevents cell death secondary to transient myocardial ischemia that occurs during reperfusion [8,9]. Numerous experimental studies have reported that TMZ prevents an excessive release of free radicals, which are particularly toxic to phospholipid membranes and are responsible for the decrease in intracellular adenosin triphosphate (ATP) concentration and the extracellular leakage of potassium and protects mitochondrial function [8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous experimental studies have reported that TMZ prevents an excessive release of free radicals, which are particularly toxic to phospholipid membranes and are responsible for the decrease in intracellular adenosin triphosphate (ATP) concentration and the extracellular leakage of potassium and protects mitochondrial function [8,10,11]. Zebrafish have hair cells on the surfaces of their bodies that function as part of the lateral line sensory system [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported that TMZ exerts a cytoprotective effect on the cardiomyocyte [1620]. Our previous works have demonstrated the cytoprotection of TMZ in an in vivo model of gentamicin-induced nephrotoxicity [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Our experiments using an in vivo model to study the effect of TMZ on the nephrotoxicity induced by gentamicin demonstrated that TMZ, when used in a 7-day pretreatment, was able to attenuate the nephrotoxic effect of this aminoglycoside [21]. …”
Section: Introductionmentioning
confidence: 99%